Adolescents do not benefit from universal school-based mindfulness interventions: a reanalysis of Dunning et al. (2022) - Galla, Brian; Karanam, Aishwarya; Pelakh, Avital; Goldberg, Simon B. (Frontiers in Psychology, 2024)
Are universal school-based mindfulness interventions an effective way to reduce risk for mental disorders and improve adolescents' lives? To answer this question, we reanalyzed data from Dunning et al.'s (2022) meta-analysis of randomized controlled trials of mindfulness interventions delivered to children and adolescents. Though Dunning et al. (2022) reported some benefits of universal mindfulness interventions, their analysis did not examine adolescents separately from children. Consequently, their conclusions may not entirely reflect the effectiveness of universal mindfulness interventions specifically for adolescents, a developmental period when mental disorders are known to increase. Using their open-access data tables, we tested impacts of 22 randomized controlled trials (N = 16,558) on eight outcome categories—anxiety/stress, attention, depression, executive functioning, mindfulness, negative behavior, social behavior, and wellbeing—at immediate post-test and longest follow-up. Our reanalysis shows that when compared to passive controls, mindfulness interventions significantly reduced trait mindfulness (d = −0.10). When compared to active controls, mindfulness interventions significantly improved anxiety/stress (d = 0.17) and wellbeing (d = 0.10). When compared to all controls combined, mindfulness interventions did not significantly improve any outcome (ds = 0.01 to 0.26). No effects of mindfulness interventions were observed at follow-up assessment. Overall, results of our analysis cast doubt about the value of existing school-based mindfulness interventions as a universal prevention strategy for adolescents.